Occupational Burnout Syndrome in the nursing context: an integrative literature review - Medeiros-Costa,Mateus Estevam (2017)
Abstract OBJECTIVE To characterize the scientific production on Burnout Syndrome in the Nursingcontext, systematizing the location where the studies were carried out, the related constructs, the employed methods and their main results. METHOD An integrative review of the literature with a bibliometric approach of articles published in Portuguese, Spanish and English between 2005 and 2016. RESULTS 106 articles wereincluded. Mostinvolvedprevalence, and were descriptive, quantitative studies performed in hospitals.The Southeastern and Southern regions of Brazil had the largest number of publications, and stress was the construct most related to burnout.Most of the studies used the Maslach Burnout Inventory to investigate the presence of the syndrome. CONCLUSION New case-control and cohort studies should be carried out.Qualitative-exploratory studies are necessary to better understand Burnout Syndrome among nursing professionals usingfocus groups or interviews, as well as comparative causal studies, with the purpose of exploring the syndrome’smanifestations.